Integrated computing technology first international conference, INTECH 2011, Sao Carlos, Brazil, May 31-June 2, 2011, proceedings - Hruschka, Estevam Rafael Jr; Watada, Junzo; Nicoletti, Maria do Carmo (Communications in computer and information science, 2011)
This book constitutes the refereed proceedings of the First International Conference on Integrated Computing Technology, INTECH 2011, held in Sao Carlos, Brazil, in May/ June 2011. The 14 revised full papers presented were carefully reviewed and selected from 103 submissions. The conference fosters discussions in integrating models, framework, designs, content,networks and the knowledge through more robust and high quality research.